Trypanocidal tetrahydrofuran lignans from Peperomia blanda - Felippe, Lidiane Gaspareto [UNESP]; Baldoqui, Debora Cristina [UNESP]; Kato, Massuo Jorge; Bolzani, Vanderlan da Silva [UNESP]; Guimaraes, Elsie Franklin; Cicarelli, Regina Maria Barreto [UNESP]; Furlan, Maysa [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Five tetrahydrofuran lignans and two known flavones were isolated from the aerial parts of Peperomia blanda. The structures of the isolated lignans were elucidated by interpretation of their spectroscopic data, including by gHMQC and gHMBC. The relative and absolute configurations of the isolates were determined from NOESY interactions and optical properties, respectively. Four of the lignans were diastercomeric whilst one was of mixed biosynthetic origin. All but one of the lignans exhibited high in vitro trypanocidal activity when assayed against epimastigotes of Trypanosoma cruzi strain Y. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Peperomia blanda; Piperaceae; tetrahydrofuran lignans; structural elucidation; trypanocidal activity